2020
DOI: 10.1038/s41416-020-0922-7
|View full text |Cite
|
Sign up to set email alerts
|

CD109 mediates tumorigenicity and cancer aggressiveness via regulation of EGFR and STAT3 signalling in cervical squamous cell carcinoma

Abstract: Background CD109 was involved in the tumorigenesis and progression of various cancers via TGF-β1 signalling and STAT3 activation. As CD109 is strongly expressed in cervical squamous cell carcinoma, this study was conducted to investigate its functional characteristics in cervical cancer. Methods CD109 expression was examined by immunohistochemistry (IHC) with cervical tissue microarray. The effects of CD109 expression were examined on migration, cell proliferation, sphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…Despite several studies having reported CD109 upregulation in a variety of malignant tumors, its molecular function and detailed regulatory mechanism are still largely unknown. Although the literature reports that CD109 is highly expressed in squamous cell carcinoma [ 13 , 20 ], our previous study identified that CD109 overexpression was specifically associated with poor survival probability in patients with lung adenocarcinoma but not with squamous cell carcinoma [ 12 ]. In the current study, we further identified that CD109 expression was significantly associated with EMT and stem-like signatures, and activation of YAP participated in the CD109-elicited EMT and cancer stemness traits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite several studies having reported CD109 upregulation in a variety of malignant tumors, its molecular function and detailed regulatory mechanism are still largely unknown. Although the literature reports that CD109 is highly expressed in squamous cell carcinoma [ 13 , 20 ], our previous study identified that CD109 overexpression was specifically associated with poor survival probability in patients with lung adenocarcinoma but not with squamous cell carcinoma [ 12 ]. In the current study, we further identified that CD109 expression was significantly associated with EMT and stem-like signatures, and activation of YAP participated in the CD109-elicited EMT and cancer stemness traits.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that CD109 is associated with and regulates the EGFR [ 11 , 12 ]. In cervical squamous cell carcinoma, CD109 expression enhanced EGFR-induced phosphorylation of STAT3, resulting in increased tumor aggressiveness and stemness activity [ 13 ]. We previously reported that CD109 is responsible for EGFR-TKI sensitivity in lung tumor cells through regulating the EGFR-AKT-mammalian target of rapamycin (mTOR) signaling cascade [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cluster of differentiation 109 (CD109) is expressed on primitive hematopoietic stem cells, activated platelets, CD4 + and CD8 + T cells, and keratinocytes ( Lin et al, 2002 ). CD109 is gaining attention as a potential biomarker as it is found highly expressed in several tumors such as squamous cell carcinoma ( Hashimoto et al, 2004 ; Zhang et al, 2005 ; Hagiwara et al, 2008 ; Mo et al, 2020 ), lung cancer ( Hashimoto et al, 2004 ; Sato et al, 2007 ; Chuang et al, 2017 ; Taki et al, 2020 ), pancreatic cancer ( Haun et al, 2014 ; Moffitt et al, 2015 ; Arias-Pinilla et al, 2018 ; Hatsuzawa et al, 2020 ), breast cancer ( Tao et al, 2014 ), glioma ( Shiraki et al, 2017 ; Minata et al, 2019 ), and many more ( Hagikura et al, 2010 ; Emori et al, 2013 , 2015 ; Yokoyama et al, 2017 ). It has been shown that high expression of CD109 in some of those tumors correlates with a bad outcome for patients ( Tao et al, 2014 ; Emori et al, 2015 ; Chuang et al, 2017 ; Yokoyama et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that high expression of CD109 in some of those tumors correlates with a bad outcome for patients ( Tao et al, 2014 ; Emori et al, 2015 ; Chuang et al, 2017 ; Yokoyama et al, 2017 ). Many signaling pathways have been proposed to be regulated by CD109 such as inhibition of TGFβ, shown in decreased SMAD2/3 phosphorylation ( Finnson et al, 2006 ; Hagiwara et al, 2008 ) and TGFβ internalization ( Bizet et al, 2011 ), impact on the activation of the JAK-STAT3 axis ( Chuang et al, 2017 ), or influence on YAP/TAZ signaling ( Minata et al, 2019 ), and more recently EGFR/AKT/mTOR ( Lee et al, 2020 ) as well as EGFR-mediated STAT3 phosphorylation ( Mo et al, 2020 ). CD109 itself is a membrane-bound protein with a glycosylphosphatidylinositol (GPI) anchor first mentioned in Sutherland et al (1991) .…”
Section: Introductionmentioning
confidence: 99%